2012
DOI: 10.1176/appi.ajp.2012.11121815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alzheimer’s Disease Risk Genes on Trajectories of Cognitive Function in the Cardiovascular Health Study

Abstract: Objective Patients with late onset Alzheimer disease (AD) vary widely in their trajectory of cognitive decline. Genetic variations in CLU, PICALM, and CR1 are associated with AD, but it is unknown if they exert their effects via altering cognitive trajectory in elderly subjects at risk for AD. Methods We developed a Bayesian model to fit cognitive trajectories in a cohort of elderly subjects and test for genetic effects. We first validated the model’s ability to detect the previously established effects of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 35 publications
0
57
1
Order By: Relevance
“…To verify the potential mechanisms underpinning the GWAS-validated association between PICALM and LOAD risk and to translate them into meaningful clinical predictors or therapies, great amounts of studies have focused on investigating association between PICALM and phenotypes relevant to AD such as specific anatomical changes [61,63,64], rate of cognitive decline [67][68][69][70][71], or progression of the disease (such as AAO) ( Table 3). For example, it has been found that a higher PICALM rs3851179 A allele frequency was consistently but weakly associated with better cognitive functioning in nondemented old men [68,72] while Sweet et al reported an association between PICALM and an earlier age at midpoint of cognitive decline [70].…”
Section: Genetics Of Picalm Gene In Admentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the potential mechanisms underpinning the GWAS-validated association between PICALM and LOAD risk and to translate them into meaningful clinical predictors or therapies, great amounts of studies have focused on investigating association between PICALM and phenotypes relevant to AD such as specific anatomical changes [61,63,64], rate of cognitive decline [67][68][69][70][71], or progression of the disease (such as AAO) ( Table 3). For example, it has been found that a higher PICALM rs3851179 A allele frequency was consistently but weakly associated with better cognitive functioning in nondemented old men [68,72] while Sweet et al reported an association between PICALM and an earlier age at midpoint of cognitive decline [70].…”
Section: Genetics Of Picalm Gene In Admentioning
confidence: 99%
“…For example, it has been found that a higher PICALM rs3851179 A allele frequency was consistently but weakly associated with better cognitive functioning in nondemented old men [68,72] while Sweet et al reported an association between PICALM and an earlier age at midpoint of cognitive decline [70]. Still, some disagreements exist [67,69,73].…”
Section: Genetics Of Picalm Gene In Admentioning
confidence: 99%
“…In addition to these polymorphisms above, a single nucleotide polymorphism (SNP) rs3818361 in CR1 was reported to be significantly associated with AD in European ancestry with P = 8.5E-08, P = 9.2E-06, and P =3.7E-14 [14][15][16]. The following studies confirmed the influence of CR1 on clinical and pathological measures of AD [17][18][19][20]. Three candidate gene studies investigated rs3818361 polymorphism in Chinese population [21][22][23].…”
Section: Introductionmentioning
confidence: 81%
“…Three independent studies investigated the rs3818361 polymorphism in Chinese population and reported a weak or negligible association between rs3818361 and AD. Growing evidence confirmed the influence of CR1 on clinical and pathological measures of AD [17][18][19][20]. Considering the important role of CR1 The quality score of included studies was scored based on the criteria developed by Clark et al [26] to evaluate the quality of genetic association studies.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have continued to support the relationship between greater cognitive impairment, more rapid cognitive decline, and AD+P. [2][3][4][5][6][7][8] AD+P is further associated with additional psychiatric and behavioral disturbances, the most frequent and troublesome of which are agitation 9 and aggression 10;11 . AD+P leads to greater distress for family and caregivers 12 , greater functional impairment, 13 higher institutionalization rates, [14][15][16][17] worse health 18 and increased mortality 19 compared to AD-P patients.…”
Section: Introductionmentioning
confidence: 99%